CHROMOSOMAL POLYMORPHISM IN BULGARIAN PATIENTS WITH REPRODUCTIVE PROBLEMS – ONE GENETIC CENTRE EXPERIENCE - Lyudmila Angelova (Peytchinski Publishing, 2021)
Chromosomal polymorphism is described as normal variants at chromosomal regions with no impact on the phenotype but a possible correlation to infertility and recurrent spontaneous abortions. The aim of this study was to evaluate the effect of the chromosomal polymorphisms involved in families with reproductive failures in the Bulgarian population. Material and methods: A total of 1733 patients with unexplained reproductive failures who visited the Laboratory of Medical Genetics – Varna, Bulgaria, (2004 - 2019) were investigated by conventional cytogenetic analysis GTG and CBG differential banding techniques and analyzed at the resolution 400-550 GTG bands. Results: Chromosomal polymorphisms were found in 173 infertile patients (9,98%). The sex distribution was 6,52% males and 3,46% females. The most frequent finding was inv(9)(qh) (23,7%). The other chromosomal variants, which were found, consisted: 9qh+/- variants (15,1%); polymorphisms on the short arms of the acrocentric chromosomes (21,4%); 16qh+ (12,7%) and 1qh+ (6,9%). Y chromosome polymorphism was found in 27,4% of the males with polymorphisms. Two rare cases of polymorphism involving the centromere regions - 19qcenh+ and 20pcenh+ were also found. Conclusion: There is growing evidence that polymorphisms may have a clinical impact on fertility and could take part in the etiology of RF. In this study, we found a significantly high percentage of polymorphisms (9,98%) among the tested patients, and they were more common among males. The statistical significance of increased incidence of chromosome variations found in our study emphasizes the need for routine evaluation of their role in families with RF in our country.